2021
DOI: 10.3390/ma14113107
|View full text |Cite
|
Sign up to set email alerts
|

Laminar N-Doped Carbon Materials from a Biopolymer for Use as a Catalytic Support for Hydrodechlorination Catalysts

Abstract: Nitrogen-doped porous carbons were prepared using a chitosan biopolymer as both a carbon and nitrogen precursor and metallic salts (CaCl2 and ZnCl2-KCl) as a templating agent with the aim of evaluating their performance as catalyst supports. Mixtures of chitosan and templating salts were prepared by simple grinding subjected to pyrolysis and finally washed with water to remove the salts. The resulting materials were characterized, showing that homogeneous nitrogen doping of carbon was achieved (7–9% wt.) thank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Fortunately, it has been reported in recent years that the introduction of inorganic salt templates can effectively tailor the pore structure of biomass carbon. 5 Soluble inorganic salts distribute uniformly in solution and penetrate the raw materials, which stabilizes the surface and provides growth sites for nucleation evenly. 6 Jain et al have shown that the mesopore ratio of biomass carbon could be significantly improved, up to 49.54%, by using ZnCl 2 during hydrothermal pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, it has been reported in recent years that the introduction of inorganic salt templates can effectively tailor the pore structure of biomass carbon. 5 Soluble inorganic salts distribute uniformly in solution and penetrate the raw materials, which stabilizes the surface and provides growth sites for nucleation evenly. 6 Jain et al have shown that the mesopore ratio of biomass carbon could be significantly improved, up to 49.54%, by using ZnCl 2 during hydrothermal pretreatment.…”
Section: Introductionmentioning
confidence: 99%